Legal Risks of Land Use and Spatial Planning in Development by Private Developers and Contractors in Indonesia: Normative Analysis, Case Studies, and FIDIC Contract-Based Mitigation Strategies - Augustinus Setijanto; Rahayu Subekti; Sarwono Hardjomuljadi (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
This article aims to comprehensively analyze the legal status of land use and spatial planning as a source of legal risk in construction projects, as well as its implications for private developers and contractors. This study uses a normative legal research method with a statutory, conceptual, and case study approach, by examining relevant laws and regulations, legal doctrine, and court decisions, including Supreme Court Decision Number 3053 K/Pdt/2011 and an apartment development dispute at the West Jakarta District Court. The results of the study indicate that land rights are not absolute and are always limited by spatial planning provisions as a public legal instrument. Weak synchronization of the RTRW/RDTR, zoning changes, and low internalization of the social function of land in development practices are dominant factors in the occurrence of disputes and project terminations. This study also found that contractors can no longer be positioned solely as technical implementers, but rather as active subjects of spatial planning compliance who potentially bear legal risks if they continue to carry out work that conflicts with spatial designations.These findings and proposals are expected to strengthen legal certainty, improve projectgovernance, and minimize disputes in private sector development.